DEVELOPMENT OF METRICS FOR PROTOCOLS AND OTHER TECHNICAL PRODUCTS - Veiga,Daniela Francescato (2015)
Objective: To develop a proposal for metrics for protocols and other technical products to be applied in assessing the Postgraduate Programs of Medicine III - Capes. Methods: The 2013 area documents of all the 48 Capes areas were read. From the analysis of the criteria used by the areas at the 2013's Triennal Assessment, a proposal for metrics for protocols and other technical products was developed to be applied in assessing the Postgraduate Programs of Medicine III. This proposal was based on the criteria of Biological Sciences I and Interdisciplinary areas. Results: Only seven areas have described a scoring system for technical products. The products considered and the scoring varied widely. Due to the wide range of different technical products which could be considered relevant, and that would not be punctuated if they were not previously specified, it was developed, for the Medicine III, a proposal for metrics in which five specific criteria to be analyzed: Demand, Relevance/Impact, Scope, Complexity and Adherence to the Program. Based on these criteria, each product can receive 10 to 100 points. Conclusion: This proposal can be applied to the item Intellectual Production of the evaluation form, in subsection "Technical production, patents and other relevant production". The program will be scored as Very Good when it reaches mean ≥150 points/permanent professor/quadrennium; Good, mean between 100 and 149 points; Regular, mean between 60 and 99 points; Weak mean between 30 and 59 points; Insufficient, up to 29 points/permanent professor/quadrennium.